EMPOWERING EDUCATION: DEVELOPING AN E-LEARNING COURSE FOR INTRODUCTION TO COMMUNICATION STUDIES AT UMN - Riatun, Riatun; Alvin, Silvanus (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aimed to explore the development of e-learning at Universitas Multimedia Nusantara (UMN), using a qualitative research method. The study collected data through interviews with key stakeholders involved in the development of e-learning at UMN. The findings suggest that the development of e-learning at UMN is necessary to improve the quality of learning and expand access to quality learning materials. The study also found that the ADDIE model was used in the development process, and three new types of content were created: virtual lightboards, scenario-based content, and gamification content. These types of content were designed to enhance student engagement and improve learning outcomes. The study concludes that the development of e-learning is essential in the current educational landscape and can benefit both students and institutions alike.